SISTEM MONITORING DAN KONTROL SUHU ALAT SANGRAI BIJI KOPI OTOMATIS BERBASIS MIKROKONTROLER - Ari Rahayuningtyas; Dadang Dayat Hidayat; Maulana Furqon; Teguh Santoso (AGROINTEK, 2023)
The roasting process influences up to 30 per cent of the aroma and taste of coffee. In this process, the coffee beans will undergo many changes ranging from a reduction in water content, weight and size to changes in colour. To be able to get the optimal aroma and taste of coffee, of course, an automation system in the roaster is needed. This study developed a microcontroller-based automatic coffee roaster monitoring system and temperature control. This study aimed to improve the performance of the roaster by substituting manual work with controlling the temperature by setting the flame on the furnace and monitoring in real-time; web/android can access it. The parameters specified in the design process consisted of time and temperature. The design method used was reengineering, which consisted of Listening to Customers, designing and building prototypes, test driving, and Evaluation. Parameter data from temperature sensor measurements could be recorded and displayed on the LCD or android.The test results showed that the average error percentage of the thermocouple was 1.43 per cent, with an average error of 0.7±0.26; these results indicated that the application of an automation system -based on a microcontroller worked properly. The average value of repeatability temperature every 5 minutes out of ten repeated measurements was  46.7±0.4oC. The performance of the roaster that has been designed was able to reduce the water content maximally by 0.165%/minute. At the same time, the rate of decline in the colour components E*, L*, a*, and b* is 0.754/min, 0.774/min, 0.754/min, 0.774/min, and 0.201/min, respectively.